Chemical composition and antioxidant activity of Origanum vulgare subsp. vulgare essential oil from Iran - M. Vazirian; M. Mohammadi; M.H. Farzaei; G. Amin; Y. Amanzadeh (Iranian Society of Pharmacognosy, 2015)
Background and Objectives: Essential oils are very complex mixture of components and their composition may vary in different species or varieties or even within the same variety. Origanum vulgare L. subsp. vulgare is one of the most distributed subspecies within the genus Origanum and has been found to be a poor-oil, categorized in cymyl, bornane or sabinyl chemotypes with higher proportion of sesquiterpenes. In this experiment, the Iranian sample was studied for the chemical composition of the oil and evaluation of its antioxidant activity. Methods: Essential oil was obtained by hydro-distillation and analyzed by GC/MS for determination of components. Antioxidant activity was evaluated by radical scavenging ability (DPPH method) and reducing power (FRAP assay). Results: The sample belonged to "thymol" chemotype with the main components as thymol (37.13%), gama-terpinene (9.67%), carvacrol (9.57%), carvacrol methyl ether (6.88), cis-alpha-bisabolene (6.80%), eucalyptol (3.82%), p-cymene (3.58%) and elemol (2.04%). The oil of plant showed very strong antioxidant activity (IC50=2.5 µg/mL in DPPH method), which was stronger than the standard antioxidants (Vit E and BHA, p